Medição de desempenho em sistemas de produção lean no contexto da construção civil - Barth, Karina Bertotto; Bazzan, Jordana; Ransolin, Natália; Formoso, Carlos Torres; Echeveste, Márcia Elisa Soares (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
This work aims to identify: (i) practices aligned to lean principles used by companies in the construction industry (ii) performance indicators used in lean systems and (iii) barriers to the implementation of these performance indicators. A survey was developed and applied as a research tool. The first version was prepared through bibliographic review and semi-structured interviews with lean production specialists. After application and refinement cycles, the final version of the questionnaire was applied to a sample of 32 companies in the construction sector, established in the state of Rio Grande do Sul/Brazil. As a contribution of the present study, the analysis of the most used practices showed that most of the companies included in the research is in an early stage of lean implementation. In addition, some of the most used practices are associated to the indicators pointed out by the participants as being more used. This relationship indicates that there is a structured attempt to mature the implementation of practices, monitored by appropriate indicators. The lack of knowledge of employees in the implementation and use of performance indicators and the lack of investment in technology are barriers to the implementation of performance indicators.